Steady‐state stomatal responses of C3 and C4 species to blue light fraction: Interactions with CO2 concentration. (30th September 2020) - Zhen, Shuyang; Bugbee, Bruce
Abstract: Blue light induced stomatal opening has been studied by applying a short pulse (~5 to 60 s) of blue light to a background of saturating photosynthetic red photons, but little is known about steady‐state stomatal responses. Here we report stomatal responses to blue light at high and low CO2 concentrations. Steady‐state stomatal conductance (gs ) of C3 plants increased asymptotically with increasing blue light to a maximum at 20% blue (120 μmol m −2 s −1 ). This response was consistent from 200 to 800 μmol mol −1 atmospheric CO2 (Ca ). In contrast, blue light induced only a transient stomatal opening (~5 min) in C4 species above a Ca of 400 μmol mol −1 . Steady‐state gs of C4 plants generally decreased with increasing blue intensity. The net photosynthetic rate of all species decreased above 20% blue because blue photons have lower quantum yield (moles carbon fixed per mole photons absorbed) than red photons. Our findings indicate that photosynthesis, rather than a blue light signal, plays a dominant role in stomatal regulation in C4 species. Additionally, we found that blue light affected only stomata on the illuminated side of the leaf. Contrary to widely held belief, the blue light‐induced stomatal opening minimally enhanced photosynthesis and consistently decreased water use efficiency. Summary Statement: Short‐term stomatal responses to pulsed blue light do not predict longer term steady‐state responses, which interacts with photosynthesis‐dependent stomatal regulation. Additionally, the blue light‐induced stomatal opening minimally enhanced photosynthesis and consistently decreased water use efficiency.